All the way to the top! The energy implications of building tall cities. (September 2017) - Hamilton, Ian; Evans, Stephen; Steadman, Philip; Godoy-Shimizu, Daniel; Donn, Michael; Shayesteh, Homeira; Moreno, Graciela
Abstract: Density of urban form may be achieved under a variety of morphological designs that do not rely on tallness alone. Tall buildings have implications on the broader urban environment and infrastructure that lower buildings would not have, e.g. wind effects, sight-lines, or over-shading. They may also have an impact on energy use for reasons of buildings-physics, construction, and occupant practices. This study uses a statistical approach of neighbourhood level data to analyse the impact of building morphology (e.g. height, volume and density) on energy demand in 12 local authorities in London. The research shows that areas marked by tall buildings use more gas after adjusting for exposures surface area, volume, number of residents and other features. The implication for energy policy and planning is building taller without increasing density may have an energy penalty.